2021
DOI: 10.1002/onco.13791
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Effects on Breast Cancer Diagnosis in Croatia: A Population- and Registry-Based Study

Abstract: Background. Our objective was to assess the effects of COVID-19 antiepidemic measures and subsequent changes in the function of the health care system on the number of newly diagnosed breast cancers in the Republic of Croatia. Subjects, Materials, and Methods. We performed a retrospective, population-and registry-based study during 2020. The comparator was the number of patients newly diagnosed with breast cancer during 2017, 2018, and 2019. The outcome was the change in number of newly diagnosed breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
(24 reference statements)
3
24
0
5
Order By: Relevance
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, after multivariate analysis, the significantly longer waiting time on list during the lockdown, was the only predictive factor for lymph node involvement progression (21). In a population-and registry-based study from Croatia, the average monthly percent change in referrals after the initial lockdown measures were introduced was −11.0%, resulting in a 24% reduction in newly diagnosed BC cases during April, May, and June compared with the same period of 2019 (22). Moreover, from the point of view of the patient, in a US national survey of BC survivors, nearly half of respondents reported delays in cancer care in the early weeks of the COVID-19 pandemic (23).…”
Section: Discussionmentioning
confidence: 99%
“…A decline in cancer diagnoses was observed in most countries where it has been investigated and for almost all tumour sites [ 10 , 11 , 14 , 24 , 25 , 26 ], in particular for those subject to screening [ 12 , 27 , 28 , 29 , 30 , 31 ]. The recovery of post-lockdown diagnosis almost never compensates for the previously observed decline [ 15 , 29 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 92%